2012
DOI: 10.1074/jbc.m112.380972
|View full text |Cite
|
Sign up to set email alerts
|

Open Conformation of Ezrin Bound to Phosphatidylinositol 4,5-Bisphosphate and to F-actin Revealed by Neutron Scattering

Abstract: Background:The structure of activated ezrin is not known. Results: We have determined the conformation of activated ezrin upon binding to PIP 2 and to F-actin. Conclusion: Activated ezrin forms more extensive contacts with F-actin than generally depicted. Significance: This study provides new insight into the mechanisms by which ezrin assembles signaling complexes at the membrane-cytoskeleton interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 90 publications
(91 reference statements)
4
58
1
Order By: Relevance
“…A similar result has been obtained via small-angle neutron scattering (SANS) using deuterated ezrin [48]. Thus, the central α-helical domain forms a coiled-coil that extends from the FERM domain which is consistent with SAXS and CD data.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A similar result has been obtained via small-angle neutron scattering (SANS) using deuterated ezrin [48]. Thus, the central α-helical domain forms a coiled-coil that extends from the FERM domain which is consistent with SAXS and CD data.…”
Section: Discussionsupporting
confidence: 74%
“…4A inset). We note that a previous study failed to distinguish between the ezrin monomer and dimer via SAXS [48]. The reason for this appears to be the Q ranged used in the previous study, which had a lower limit of 0.014 Å -1 and hence the key difference between monomer and dimer SAXS (the upsweep below 0.02 Å -1 ) is effectively missing in their data.…”
Section: Solution Structure Of Full-length Ezrin Monomer and Dimer Bymentioning
confidence: 64%
“…4E. Similarly, it was reported that conformational opening of ezrin upon binding to PIP2 results in more extensive contacts with Factin (Jayasundar et al, 2012). Since PIP2 localization is restricted to the transcriptionally active regions in the nucleolus, we suggest that a particular hydrophobic proteinlipid-RNA environment might exist in that particular region and contribute to the detergent-resistant nuclear PIP2 pools, which were shown to make up to 40% of the total PIP2 mass (Vann et al, 1997).…”
Section: Pip2 Co-localizes With Rrna Nascent Transcripts In Nucleolimentioning
confidence: 93%
“…Interestingly, the affinity for the full-length protein or for the FERM domain were comparable, indicating that the C-TER and the α-helix did not impair the interaction. Also another recent study from Jayasundar et al [81] shows using small angle neutron scattering (SANS) that PIP2 in solution (micellar in this case) can interact with ezrin and lead to, more than a conformational change, to full activation, ie ezrin can interact with actin.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 97%
“…Interestingly, the affinity for the full-length protein or for the FERM domain were comparable, indicating that the C-TER and the α-helix did not impair the interaction. Also another recent study from Jayasundar et al [81] shows using small angle neutron scattering (SANS) that PIP2 in solution (micellar in this case) can interact with ezrin and lead to, more than a conformational change, to full activation, ie ezrin can interact with actin.The conformational change of ezrin evidenced with PIP 2 dispersed in solution can be challenged in a cellular context, as PIP 2 is not available in its soluble form or even in its micellar form. Are such conformational changes present when PIP 2 is inserted in membranes?…”
mentioning
confidence: 97%